ANALISIS KEPUTUSAN PETANI DALAM PENGAMBILAN KREDIT SEKTOR PERTANIAN KECAMATAN LAMAKNEN KABUPAEN BELU - Ernestina Lika (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to analyze the decision of farmers in taking credit for farmers.The research model is quantitative using a questionnaire, and the resultscollected from respondents are processed using SPSS 21 software withdiscriminant analysis obtained the difference between the two groups of creditand non-credit farmers. The sample used is a probability sampling technique of125 respondents. This non-metric model is carried out to find out the decisionnot to take credit (0) as many as 55 respondents or 88.7% while as many as 7respondents or 11.1% e group taking credit (1). Meanwhile 52 respondents or82.5% of respondents in the group taking credit (1) and as many as 11respondents or 17.5% of respondents moving to the group not taking credit.